Targeting of chikungunya virus envelope protein as an antiviral strategy to inhibit cell entry - Fidalgo, Daniela Marina (2019)
Chikungunya virus (CHIKV) is a member of the Alphavirus genus of the Togaviridae family. It is transmitted by mosquitoes of the Aedes species and is characterized by severe polyarthralgia that may last for months. Until today, no antiviral agent or vaccine has been approved for treatment or prevention of CHIKV infection. Virus invasion of the host cells is mediated by the envelope proteins, E1 and E2. Antiviral targeting of virus envelope proteins is an effective strategy for therapeutic intervention. Our goal was to design and synthesize lead compounds that can interact with a druggable pocket at the interface of the E1-E2 heterodimer. First, we used Autodock Vina to perform a virtual screening of commercially available compounds from Maybridge and Chembridge libraries. Selected compounds were bought or synthesized, and then tested against CHIKV using a reporter virus assay. Compound CHIK-1 showed a good antiviral activity (EC50 1,0 μM) and a selectivity greater than 50. Time of drug addition assays showed that CHIK-1 exerts its antiviral activity in the early stages of the viral life cycle. As CHIK-1 has a chiral center, we analyzed the antiviral activity of R and S enantiomers. To this end, we performed an enantioselective synthesis using as intermediary enantioenriched epoxides that were prepared using a methodology described in the literature. Based on molecular dynamics simulation (MD), forty-one CHIK-1 derivatives were designed and synthesized. Seven derivatives displayed low micromolar activity using a recombinant CHIKV-GFP reporter assay. Furthermore, pharmacokinetic in vitro and solubility assay for active compounds are currently ongoing. In conclusion, we uncovered novel entry inhibitors against CHIKV by prospective docking-based virtual screening and MD optimization. Now, we are seeking the solubility and stability optimization of lead compounds.